Evidence from International Financial Markets on Stock Market Liquidity During Times of Distress and Its Consequence - S.K. Sahani; K.S. Prasad; G.P. Paudel; S.K. Tiwari (International Journal of Advanced Technology and Social Sciences, 2023)
Old-fashioned ways to price things believe that the buying and selling of goods happen without any difficulties and there is always enough money available in the market this way of thinking has some weaknesses because it can't clarify all the issues that come with the lack of buyers and sellers in the security market. This study wanted to understand how easy it is to sell stocks during tough times in the economy. We used a special model to study how easy it was to buy and sell things in different stock markets during two big events - the financial crisis in 2007-2008 and the Covid-19 outbreak. We looked at five specific stock markets: CAC 40, DAX, JSE, Nasdaq Index, and Nikkei-225. The time when we looked at things was from January 1, 2020 to December 31, 2021 and from December 1, 2007 to June 30, 2009. Despite the financial crisis, some financial markets had enough money to keep trading. However, the Nasdaq index was an exception and couldn't keep up. On the other hand, all the money markets we looked at had a hard time being able to turn investments into cash during the covid-19 pandemic. This could be because people need to have more money to trade and it's harder to know everything about what's happening in the market